Aliphatic polyamides (nylons): Interplay between hydrogen bonds and crystalline structures, polymorphic transitions and crystallization. Issue 4 (30th June 2021) - Puiggalí, Jordi
Abstract: Aliphatic polyamides (nylons) constitute a family of polymers with outstanding properties and multiple applications. Despite the intensive research studies carried out with nylons, there are still multiple unsolved questions concerning crystallization processes, crystalline structures, polymorphic transitions, and crystalline morphologies. Constrains imposed by the strong intermolecular interactions affect the amorphous state, the rigid amorphous phase, the molecular folding, the morphology and obviously the crystalline structure. Some of these relevant points are discussed in the present work. Abstract : The establishment of hydrogen bonds plays a relevant role in the crystalline structure of nylons, their lamellar and spherulitic supramolecular orders, and their amorphous state. Different polymorphic forms with 1H‐, 2H‐ and 3H‐bonding directions have been described for nylons depending on their constitutive units and thermal and mechanical treatments to which they have been submitted. Despite the multiple research efforts carried out, multiple concepts involving the strong intermolecular interactions and their temperature dependence still remain unclear.